Energy efficient routing techniques with guaranteed reliability based on multi-level uncertain graph - Wendi Nie; Yaoxin Duan; Kaijie Wu; Qingfeng Zhuge; Sha, Edwin H. M. (IEEE Symposium on Embedded Systems for Real-Time Multimedia (Print), 2014)
In recent years, an emerging low-power system "wireless sensor networks (WSNs)" attracts significant research interests. The energy of the distributed sensors is an essential constraint in such a complex distributed embedded system. Routing techniques in WSNs always follow a high-performance and energy-efficient way. However, conventional routing schemes of WSNs generally do not take the timing and reliability requirements into account when making routing decisions to prolong the lifetime of WSNs. Moreover, due to environmental factors such as temperature, humidity and signal interference, the bandwidths of links in a WSN various from time to time like random variables, which demands special considerations when timing and reliability requirements are presented for routing. In this paper, we introduce a graph model called Multi-level Uncertain Graph (MUG) to deal with the situation. Based on the MUG model, we define the new problem as the Energy-Balanced Transmission (EBT) Problem, and propose a EBT-Solver to maximize the lifetime of the WSN subject to timing and reliability constraints. Experimental results show that EBT-Solver solves EBT problem to the best advantage of energy balance and network's lifetime.